Oral Presentations 2016 AANS Annual Scientific Meeting Chicago, IL • April 30–May 4, 2016Published online April 1, 2016; DOI: 10.3171/2016.4.JNS.AANS2016abstracts (Journal of Neurosurgery, 2016)
Osteopetrosis is a rare skeletal dysplasia characterized by impaired osteoclastic bone resorption, leading to dense but brittle bones prone to pathological fractures. Although fractures in the appendicular skeleton are well described, cervical spine involvement, particularly atlantoaxial rotatory subluxation is rare in children. The authors present the case of a 7-year-old boy with autosomal recessive osteopetrosis who developed torticollis and restricted neck motion following minor trauma. Imaging revealed rotatory C1-2 subluxation with bilateral C2 pars interarticularis fractures. Surgical fixation was performed using a posterior C1-2 approach with lateral mass and pars screws. Low-speed drilling and avoidance of malleting were used because of sclerotic bone. The construct was augmented with autologous graft and demineralized bone matrix. The patient achieved early postoperative mobilization and resolution of torticollis and maintained neurological integrity throughout follow-up. This case represents the first reported pediatric case of osteopetrosis with combined rotatory C1-2 instability and bilateral pars fractures with nonunion, and it was managed successfully with isolated posterior fixation. It highlights the feasibility and safety of surgical stabilization in carefully selected cases of chronic instability despite the challenging bone biology. This report expands the current understanding of cervical spine trauma in osteopetrosis and offers technical guidance for operative planning. https://thejns.org/doi/10.3171/CASE26479.